Suitability of customer relationship management systems for the management of study participants in biomedical research - Schwanke, J; Rienhoff, O; Schulze, T G; Nussbeck, S Y (Methods of information in medicine, 2013)
Longitudinal biomedical research projects study patients or participants over a course of time. No IT solution is known that can manage study participants, enhance quality of data, support re-contacting of participants, plan study visits, and keep track of informed consent procedures and recruitments that may be subject to change over time. In business settings management of personal is one of the major aspects of customer relationship management systems (CRMS). To evaluate whether CRMS are suitable IT solutions for study participant management in biomedical research. Three boards of experts in the field of biomedical research were consulted to get an insight into recent IT developments regarding study participant management systems (SPMS). Subsequently, a requirements analysis was performed with stakeholders of a major biomedical research project. The successive suitability evaluation was based on the comparison of the identified requirements with the features of six CRMS. Independently of each other, the interviewed expert boards confirmed that there is no generic IT solution for the management of participants. Sixty-four requirements were identified and prioritized in a requirements analysis. The best CRMS was able to fulfill forty-two of these requirements. The non-fulfilled requirements demand an adaption of the CRMS, consuming time and resources, reducing the update compatibility, the system's suitability, and the security of the CRMS. A specific solution for the SPMS is favored instead of a generic and commercially-oriented CRMS. Therefore, the development of a small and specific SPMS solution was commenced and is currently on the way to completion.